Menggugat pemerintahan otoriter : kumpulan pembelaan Ketua Umum Dewan Mahasiswa ITS [Harun Alrasyid], Sekretaris Umum Dewan Mahasiswa ITS dan pembela-pembelanya - Alrasyid, Harun (Forum Pembelaan Mahasiswa Indonesia, 1979)
Collection of speeches presented during the 1979 political trials in Surabaya in defense of Harun Alrasyid and Mohammad Sholeh, the Chairman and General Secretary of the Student Council of the Surabaya Institute of Technology.